Marine oligotrophication due to fine sediments and nutrient starvation caused by anthropogenic sediment and water retention in large rivers: the Nile damming case - Herut, Barak; Guy-Haim, Tamar; Almogi-Labin, Ahuva; Fischer, Helmut W.; Ransby, Daniela; Sandler, Amir; Katz, Timor; Avnaim-Katav, Simona (Frontiers in Marine Science, 2023)
In the last two centuries, human activities radically reduced the transport of suspended sediments and water to marine systems, mainly in the Northern Hemisphere, whereas complete sediment retention has been reported for the Nile River after the construction of the Aswan High Dam (AHD). Here, we focused on changes in the inner-shelf sediments exposed most to the pre-AHD flood plume at the distal part of its littoral cell as a predictor of ecological response to large rivers fragmentation. Substantial reduction of fine (15-40%) and increase in coarse (~8 fold) sediment accumulation rates, increase in CaCO3 (~50%), decrease in autochthonous and total organic carbon (OC) and change in the benthic foraminifera assemblage towards more OC-sensitive species, suggests enhanced oligotrophication trend. The reduced nutrient fluxes and OC accumulation and the coarsening of the shelf sediments inhibit the retention of “blue” carbon. Combined with fast climate change warming and salinization, rivers fragmentation may produce essential implications to the Eastern Mediterranean ecosystem via benthic oligotropication processes.